The Role of Political Parties in Indonesia’s Democratic Transition: Strengths, Weaknesses, and Future Directions - Muhammad Akbar Purwanto; Justico Adam Nusantara; Rajesh Joshi (Indonesian Political Transformation, 2025)
Political parties have played a central role in Indonesia's democratic transition since the fall of the New Order regime. This paper critically examines the role of political parties in consolidating Indonesia’s democracy, assessing their ability to represent diverse interests, foster political participation, and provide effective governance. The study explores the evolution of Indonesia’s party system, the challenges of party fragmentation, and the growing influence of political dynasties and oligarchs. Through an analysis of party strategies, electoral outcomes, and political communication, the paper assesses how political parties have shaped both the national political discourse and local governance. The research also explores the growing trend of populist and identity-based politics, examining the impact on party development and the quality of democratic processes. The contribution of this paper lies in its comprehensive evaluation of the strengths and weaknesses of Indonesia's political parties and its recommendations for improving party system integrity and political accountability.